Effect of Cooling Media on Steel Hardness ST 37 On Conventional Lathe Process - Erizon, Nelvi; Ardiyansyah, M Iksan; Jasman, Jasman; A, Yufrizal (Universitas Negeri Padang, 2018)
This study aims to determine the type of air cooling media, soluble oil, and air to the result on lathe ST 37 steel. The cooling medium is very important to maintain boring tool deformation and can add product quality. In the process lathe of friction between the workpiece and chisel cut that can produce overheating and influence on the result of the slice boring tool on the workpiece. The research that will be carried out is experimental research with variables that are controlled that is feeding, deep of a cut, and spindle rotation and examination of the hardness of the specimen on the object before done lathe. The sample in this study which is ST 37 steel with diameter 25 mm and length 60 mm as many as 9 specimens which will be done lathe with different type media kind inprocess working. To know influence the type of cooling medium against steel ST 37 is done brinnel hardeness test using test equipment hardness tester. Of the 9 specimens lathe will be determined 3 points to do hardeness tests. From the result of hardness test and analysis obtained from hardness test on steel ST 37 average data that is use of soluble refrigerant media that produce a very good cooling at the time of the lathe process. The results of research is obtained that the use of soluble refrigerant media is the best with an average hardness of 224.10 kg / mm². On the lathe process, the cooling media has oil content will be able to maintain the scores hardness and time-worn on boring tool. Thus to maintain the hardness values can be used soluble oil cooling media and to increase the hardness values of workpieces can be used air cooling media.